Organization of the mitotic chromosome - Naumova, Natalia (2013)
Mitotic chromosomes are among the most recognizable structures in the cell, yet for over a century their internal organization remains largely unsolved. We applied chromosome conformation capture methods, 5C and Hi-C, across the cell cycle and revealed two alternative three-dimensional folding states of the human genome. We show that the highly compartmentalized and cell-type-specific organization described previously for non-synchronous cells is restricted to interphase. In metaphase, we identify a homogenous folding state, which is locus-independent, common to all chromosomes, and consistent among cell types, suggesting a general principle of metaphase chromosome organization. Using polymer simulations, we find that metaphase Hi-C data is inconsistent with classic hierarchical models, and is instead best described by a linearly-organized longitudinally compressed array of consecutive chromatin loops.